2017
DOI: 10.1096/fj.201601264rrr
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic role of the spliced somatostatin receptor sst5TMD4 variant in prostate cancer

Abstract: sst5TMD4, a splice variant of the sst5 gene, is overexpressed and associated with aggressiveness in various endocrine-related tumors, but its presence, functional role, and mechanisms of actions in prostate cancer (PCa)-the most common cancer type in males-is completely unexplored. In this study, formalin-fixed, paraffin-embedded prostate pieces from patients with localized PCa, which included tumoral and nontumoral adjacent regions ( = 45), fresh biopsies from patients with high-risk PCa ( = 52), and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 44 publications
6
80
0
Order By: Relevance
“…It has been demonstrated that the expression of some components of the SST system, especially sst variants, are dysregulated in PCa tissue and associated with the aggressiveness of tumor cells, which highlights the putative utility of these components as novel biomarkers and therapeutic targets to develop pharmacologic strategies for this pathology. In this sense, SST receptor subtype 1 (sst1, SSTR1 ) has been described as an important molecule in several types of cancer, such as colon cancer, where it seems to play a significant role and is associated with some aggressiveness features .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the expression of some components of the SST system, especially sst variants, are dysregulated in PCa tissue and associated with the aggressiveness of tumor cells, which highlights the putative utility of these components as novel biomarkers and therapeutic targets to develop pharmacologic strategies for this pathology. In this sense, SST receptor subtype 1 (sst1, SSTR1 ) has been described as an important molecule in several types of cancer, such as colon cancer, where it seems to play a significant role and is associated with some aggressiveness features .…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In fact, somatostatin analogs (eg, the sst2-preferring octreotide and lanreotide, and the pan-sst ligand pasireotide) are currently being used to treat some of these pathologies, such as pituitary adenomas and NETs, highlighting the clinical relevance of this system. [25][26][27] It has been demonstrated that the expression of some components of the SST system, especially sst variants, are dysregulated in PCa tissue and associated with the aggressiveness of tumor cells, [28][29][30] which highlights the putative utility of these components as novel biomarkers and therapeutic targets to develop pharmacologic strategies for this pathology. In this sense, SST receptor subtype 1 (sst1, SSTR1) has been described as an important molecule in several types of cancer, such as colon cancer, where it seems to play a significant role and is associated with some aggressiveness features.…”
Section: Introductionmentioning
confidence: 99%
“…All biopsy specimens were analyzed by experienced urologic pathologists according to the International Society of Urological Pathology 2005 modified criteria [14]. Tumor regions (n = 84) were identified from the Formalin-Fixed Paraffin-Embedded (FFPE) samples by expert urologic pathologists as previously reported [15,16] and used to isolate RNA and perform gene expression analyses. The FFPE pieces were taken from radical prostatectomies (patients belonging to cohort 3).…”
Section: Cohortmentioning
confidence: 99%
“…DU145 and LNCaP cell lines were obtained from American Type Culture Collection (ATCC; Manassas, VA, USA), cultured according to the manufacturer's instructions, validated by analysis of short tandem repeats sequences using GenePrint 10 System (Promega, Barcelona, Spain) and checked for mycoplasma contamination by PCR as previously reported [8,16]. DU145 cells were selected for functional in vitro and in vivo analyses based on its high expression levels of In1-ghrelin, the main oncogenic element of the ghrelin axis in prostate cancer, which is also a putative target of GOAT [8].…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation